Cohesive and adhesive healing evaluation of asphalt binders by means of the LASH and BBSH tests. (3rd May 2021) - Wang, Chao; Chen, Yifang; Gong, Guanyu
Highlights: The cohesive and adhesive binder healing are compared by the LASH and BBSH tests. A crack growth approach is investigated to define the cohesive healing recovery. The recovery of crack length is recommended for binder cohesive healing assessment. The water and granite substrate show positive effects on binder adhesive healing. Abstract: Generally, the cohesive healing within the asphalt composites and the adhesive healing from the asphalt-aggregate interface always occur simultaneously in the asphalt concrete with growing damage. This study aims to investigate the cohesive and adhesive healing behaviors of asphalt binder respectively by utilizing the newly developed linear amplitude sweep based healing (LASH) and binder bond strength based healing (BBSH) tests. Seven unmodified asphalt binders and one styrene–butadienestyrene (SBS) polymer modified binder are selected in this study. A fracture mechanics based crack growth approach is proposed to define the cohesive healing recovery in the LASH test with two percent healing parameters, in terms of the % H a of the crack length recovery and the % H A of the sample intact area recovery. In pre-failure conditions, the measured % H a can at least reach beyond 30% while the % H A is normally within 30% for tested binders. Meanwhile, the % H a results show more consistent trends to the traditional simplified-viscoelastic continuum damage (S-VECD) based LASH data interpretation. Furthermore, the cohesive failure occurrence is verified to significantly impact the healing performance comparison. The cohesive healing behaviors of neat and SBS binders respectively in pre-failure and post-failure conditions are distinguished to each other, which are validated either from S-VECD or crack growth approaches. Regarding to the binder adhesive healing behavior, it is observed that the presence of water and the using of granite substrate generally have positive effects on adhesive healing recovery in the BBSH tests. The SBS modification generally displays lower adhesive healing percentages than the neat binders especially in the wet conditions. Though no clear relationships can be found between the cohesive and adhesive healing behaviors in this study, it is recommended to quantify the binder contribution to the adhesive healing process in the future work.